Model Evakuasi Erupsi Gunung Merapi Menggunakan Safevolcano dengan Visualisasi Web Berbasis Spasial dan Aplikasi Android - Aryant, Ivan, Dr. Kuswaji Dwi Proyono, M.Si, Jumadi, S.Si, M.Sc (2016)
Geographic information system technology in disaster management could help with extenstion of sharing nircable data technology via internet access. Sharing spasial data in mobile device hopeable to maximize the decision as first importance step in disaster management. The characteristic of mobile device is portable, which mean it can be interactif map as true orient to evacuation site safe through least-cost route. This study is a replica model of evacuation scenarios eruption Merapi Volcanoes in 2010 with the spatial perspective and to how consume it into device based location-focused technology. The goal of this research are: 1) determine the eruption Merapi Volcanoes evacuation model used to SAFEVolcano tools that distribute the selection evacuation sites, selection allocation victims, and evacuation route in some scenarios, and; 2) to know the result of eruption Merapi Volcanoes evacuation model that integrated by web and android applications which mean interactive map to evacuate the victims of the eruption Merapi Volcanoes disaster. This research used to analysis secondary method, field check, GIS analysis tools, and web developing. Secondary data and check the evacuation site are GIS tools SAFEVolcano input with else parameters processing which output shared to the web and android package applications virtualize via internet access. This research results are: 1) first scenario, SAFEVolcano distribute 144.137 populations at risk that in 38 villages (polygon feature) is allocated to 400 evacuation sites safe (point feature) throw by 426 least-cost paths; second scenario, SAFEVolcano distribute 232.442 populations at risk that in 64 villages (polygon feature) is allocated to 715 evacuation sites safe (point feature) throw by 779 least-cost paths; third scenario, SAFEVolcano distribute 901.096 populations at risk that in 137 villages (polygon feature) is allocated to 1.352 evacuation sites safe (point feature) throw by 1.466 least-cost paths; and 2) the third divices (server computer, client computer, and android devices) can connect each other especially to share data from server computer then the client computer and android device can communicate in web or android apps. Application test for 30 users show the flow data virtualization as well, but the server computer can't load big data quicly because low speck of the server computer. Keywords: technology, spatial data, mobile, sharing, SAFEVolcano, webGIS, android.